Peran Zakat dan Wakaf dalam Meningkatkan Kesejahteraan Masyarakat: Analisis SWOT - Umi Sangadah; Lusi Indriyani; Andre Putra Pratama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One of the main objectives of economic development in many nations, including Indonesia, is to improve societal welfare. Within this framework, zakat and waqf have great promise as Islamic social financial tools that alleviate poverty and inequality in society. With their solid theological and historical roots in Islamic tradition, zakat and waqf have long been employed to promote social and economic prosperity. Nonetheless, there are a number of obstacles facing the collection and administration of zakat and waqf in Indonesia, including poor public confidence in zakat management organisations and a lack of public awareness of the duties associated with zakat and the advantages of waqf. Using a SWOT analysis, this study intends to examine the roles that zakat and waqf play in enhancing societal wellbeing. The strengths, limitations, possibilities, and dangers encountered in the management of zakat and waqf are identified in this analysis, which also offers strategic recommendations to maximise the potential of zakat and waqf in promoting social and economic development. It is anticipated that the findings of this study will significantly aid in the creation of zakat and waqf management methods and policies that are more effective and efficient.